FAKTOR FAKTOR YANG MEMPENGARUHI INTENSI KEWIRAUSAHAAN MAHASISWA POLITEKNIK - Bambang Hendrawan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
The research objective is to identify influence factors that influence student entrepreneurial intention or student intention to become entrepreneur particularly for polytechnic students. This is very interisting because at the beginning, the student who going study to polytechnic just only expect to get a job quickly after their graduated. The sampling method of this reseach used purposive sampling whereas 165 selected samples were taken from up to 4 semester student of all study program that were participated in entrepreneurship learning program at Batam Polytechnic . The methods used for analysis were descriptive analysis and multiple linier regression analysis and processed by SPSS Software Tools. The student entrepreneurial intention would represented as dependend variable meanwhile the independend variable come from factors that represent sosio-demographic and environment characteristic of the students. The result of this research indicates that the existence of some factors particularly the environmental factors such as student entrepereneurship program, facilities and mentoring support by campus, parent support and existence of entrepreneur association having significant correlation statistically to students entrepreneurial intention of Polytechnic Students. It means those factors tend to higher influence for student to become entrepreneur. Meanwhile, the sosio-demographic factors such as gender, study program background, level of education program, parent occupation, have no significant correlation. The finding of research also was affirming the role of campus, parent and entepreuner communities have very important to support the student to become prospective entrepreneur. The finding related the role of those parties implies campus structurally should develop an integrated relationship model between the parties that allow the parties give optimal contribution or support, so therefore it should be maximized the positive effect for student entrepreneurial intention in the future.